A quantitative approach to retrieve delamination extension from thermal images recorded during impact tests. (December 2018) - Meola, Carosena; Boccardi, Simone; Carlomagno, Giovanni Maria
Abstract: This work is concerned with the evaluation of the impact damage extension in composites from thermal images recorded during inline monitoring of impact tests. A new method is developed which derives from the previously conceived Noise Correction Reference (NCR) approach and includes the thermal diffusion time, leading to a new NCRD method. Starting from the correspondence between warm area and delamination, the NCR basically consists in a comparison between an average Δ T image taken after impact with one taken before and involves a given set of images, acquired in temporal sequence during impact tests. A critical aspect of this method resides in the choice of the post impact images to be involved in the average because of the many parameters such as type of material, geometry and impact energy, which may affect the related thermal effects. Until now, this choice has been dictated by empirical considerations about the heat diffusion time of a given material. The aim of this work is to revise and improve the previous criterion. As a main novelty, the heat diffusion time is introduced which enhances the accuracy of the warm area estimation to be used for impact delamination evaluation; the suggested method is named NCRD. Highlights: Impact testing of composites is inline monitored with infrared thermography. The visualized thermal signatures are related to impact damage. A method is proposed to evaluate delamination extension from thermal images. The thermal diffusion time is considered in the proposed method. The thermal diffusion time is extracted from thermal images.